Persistence of Ebola virus after the end of widespread transmission in Liberia: an outbreak report. Issue 9 (September 2018) - Dokubo, Emily Kainne; Wendland, Annika; Mate, Suzanne E; Ladner, Jason T; Hamblion, Esther L; Raftery, Philomena; Blackley, David J; Laney, A Scott; Mahmoud, Nuha; Wayne-Davies, Gloria; Hensley, Lisa; Stavale, Eric; et al.
Summary: Background: Outbreak response efforts for the 2014–15 Ebola virus disease epidemic in west Africa brought widespread transmission to an end. However, subsequent clusters of infection have occurred in the region. An Ebola virus disease cluster in Liberia in November, 2015, that was identified after a 15-year-old boy tested positive for Ebola virus infection in Monrovia, raised the possibility of transmission from a persistently infected individual. Methods: Case investigations were done to ascertain previous contact with cases of Ebola virus disease or infection with Ebola virus. Molecular investigations on blood samples explored a potential linkage between Ebola virus isolated from cases in this November, 2015, cluster and epidemiologically linked cases from the 2014–15 west African outbreak, according to the national case database. Findings: The cluster investigated was the family of the index case (mother, father, three siblings). Ebola virus genomes assembled from two cases in the November, 2015, cluster, and an epidemiologically linked Ebola virus disease case in July, 2014, were phylogenetically related within the LB5 sublineage that circulated in Liberia starting around August, 2014. Partial genomes from two additional individuals, one from each cluster, were also consistent with placement in the LB5 sublineage. Sequencing data indicate infection with a lineage of the virus from a former transmission chain in the country. Based on serology and epidemiological and genomic data, the most plausible scenario is that a female case in the November, 2015, cluster survived Ebola virus disease in 2014, had viral persistence or recurrent disease, and transmitted the virus to three family members a year later. Interpretation: Investigation of the source of infection for the November, 2015, cluster provides evidence of Ebola virus persistence and highlights the risk for outbreaks after interruption of active transmission. These findings underscore the need for focused prevention efforts among survivors and sustained capacity to rapidly detect and respond to new Ebola virus disease cases to prevent recurrence of a widespread outbreak. Funding: US Centers for Disease Control and Prevention, Defense Threat Reduction Agency, and WHO.